Methodological support for formation of resource requirements in multi-project environment - Dotsenko, Nataliia (Technology audit and production reserves, 2019)
The object of research is the processes of human resource management of projects in a multi-project environment. In a multi-project environment, the level of team autonomy within an organization can be different, and the lack of a resource control system at the portfolio level reduces the effectiveness of critical organization knowledge management. The main hypothesis of the study is the assumption that an adequate understanding of customer requirements is crucial to ensure project management, and the effectiveness of human resource management in a multi-project environment depends on the effectiveness of determining resource requirements in the formation of project teams. During the study, methods of system analysis are used in the study of human resource management processes and modeling of the formation of requirements for the project team. A competency-based approach is also used in the development of a method for generating resource requirements and an optimization theory apparatus for formulating and solving problems of forming project teams in multi-project environment under given restrictions. In order to reduce the likelihood of resource conflicts, it is proposed to analyze the initial data when forming requirements for the project team. Coordination of resource requirements at the stage of team formation will reduce the risks of resource conflicts during the implementation of projects included in the project portfolio. Possible results of the analysis of stakeholder requirements are considered. A method for generating resource requirements in a multi-project environment is proposed, based on an analysis of stakeholder interest in human resource management processes, taking into account the loyalty of stakeholders, which, unlike existing ones, takes into account the consistency of resource constraints defined by stakeholders. This will allow the formation of agreed requirements for the resources of projects and programs. The generated requirements are the initial data for building project teams using the proposed method of forming teams in a multi-project environment. A model of the process of forming requirements for the project team is built. For the purpose of automation, a software package has been developed that allows to generate options for building project teams with an indication of the characteristics of the options, which will further optimize the composition of the team.